Atheism, religion and enlightenment in pre-revolutionary Europe - Curran, Mark ca. 20./21. Jh. (A Royal Historical Society publication, 2012)
This book examines the reception of the works of the baron d'Holbach throughout francophone Europe. It insists that d'Holbach's historical importance has been understated, argues the case for the existence of a significant 'Christian Enlightenment', and much more